The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0092009
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Expression Is Dynamically Regulated in the Germinal Center and Bone Marrow Plasma Cells Are Diminished in Its Absence

Abstract: CD73 catalyzes the conversion of extracellular nucleosides to adenosine, modulating inflammatory and T cell responses. Elevated expression of CD73 marks subpopulations of murine memory B cells (MBC), but its role in memory development or function is unknown. Here, we demonstrate that CD73 is progressively upregulated on germinal center (GC) B cells following immunization, is expressed at even higher levels among T follicular helper cells, but is absent among plasma cells (PC) and plasmablasts (PB). We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 57 publications
5
57
0
Order By: Relevance
“…It seems likely, then, that IgM memory cells are regulated via adenosine receptors, which likely function by regulating inflammation, as has been reported for CD73. However, our initial studies of CD73-deficient mice have failed to reveal a requirement for this receptor for the generation or function of IgM memory cells (unpublished data), findings which are consistent with other published studies that have reported relatively modest effects of CD73-deficiency in B cells [75]. Nevertheless, further investigation into a role for adenosine and related receptors on memory B cells will likely be informative.…”
Section: Transcriptome Analysessupporting
confidence: 84%
“…It seems likely, then, that IgM memory cells are regulated via adenosine receptors, which likely function by regulating inflammation, as has been reported for CD73. However, our initial studies of CD73-deficient mice have failed to reveal a requirement for this receptor for the generation or function of IgM memory cells (unpublished data), findings which are consistent with other published studies that have reported relatively modest effects of CD73-deficiency in B cells [75]. Nevertheless, further investigation into a role for adenosine and related receptors on memory B cells will likely be informative.…”
Section: Transcriptome Analysessupporting
confidence: 84%
“…Consistent with a role for CD73 in CSR, B cells from CVI patients show very low CD73 expression, and CD73 on neonate B cells gradually increases during the first 6 months of life, correlating with their ability to make IgG. In vivo immunization of CD73‐deficient mice, however, revealed only slightly delayed or normal isotype switched responses …”
Section: B Cellsmentioning
confidence: 60%
“…Studies with CD80-deficient mice have showed that CD80 plays an important role in regulating interactions between B and T cells during early and late GC formation and lack of CD80 expression leads to an impaired development of long lived plasma cells (Good-Jacobson et al, 2012). Expression of CD73 is also upregulated in highly functional MBCs and its deletion prevented the development of LLPCs in the bone marrow (Conter et al, 2014). To determine whether blood stage infection perturbed the expression of CD80 and CD73, mice were infected with parasites as described above and CSP-specific B cells were analyzed for surface expression of these phenotypic markers 30 days later.…”
Section: Resultsmentioning
confidence: 99%